2011
DOI: 10.2478/s13545-012-0006-2
|View full text |Cite
|
Sign up to set email alerts
|

Potamozooplankton communities in three different outlets from mesotrophic lakes located in lake-river system

Abstract: Qualitative and quantitative composition of potamozooplankton was studied in three outlets from mesotrophic lakes. The greatest taxonomic and quantitative similarity of zooplankton occurred between the outflows of the second and third lake, located in the lake-river system. The farther the lake was located in the lake-river system, the greater was the quantity of zooplankton in the outflow. Within a short distance between the outflow and the downstream section, there was a strong reduction of cladocerans' comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
3
10
0
1
Order By: Relevance
“…The higher the values of the above parameters, the lower the reduction in crustacean biomass. Some authors studying the influence of hydrological conditions of outlets or streams on the composition of zooplankton have reported a positive correlation between hydrological variables and communities of plankters, especially the large taxa (Campbell 2002, Czerniawski & Domagała 2012. Perhaps, in the outflow sections where current velocity and discharge are high, the pressure of planktivorous fish on zooplankton is smaller, because of high current speed that drifts zooplankton faster, making it hard to reach (Czerniawski & Domagała 2010b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The higher the values of the above parameters, the lower the reduction in crustacean biomass. Some authors studying the influence of hydrological conditions of outlets or streams on the composition of zooplankton have reported a positive correlation between hydrological variables and communities of plankters, especially the large taxa (Campbell 2002, Czerniawski & Domagała 2012. Perhaps, in the outflow sections where current velocity and discharge are high, the pressure of planktivorous fish on zooplankton is smaller, because of high current speed that drifts zooplankton faster, making it hard to reach (Czerniawski & Domagała 2010b).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of abundance and biomass of chydorids reached over 80% while that of bosminids reached over 70%. Chang et al (2008), Czerniawski & Domagała (2012), and Czerniawski & Pilecka-Rapacz (2011) have also reported a great reduction in the density and biomass of zooplankton representing the same taxa in the outflows from lakes and artificial reservoirs, reaching even 100%, which, as mentioned above, should be related to the pressure of planktivorous fish. Significant reduction of communities of small cladocerans such as bosminids and chydorids by fish does not agree with the results of experimental studies of some authors who reported that the presence of fish had no negative effect on the density of Bosmina sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…harpae and Ch. sphaericus À which occur in small ponds and may be dominant in the littoral zone À can also occur in the rheopelagial (as potamoplankton) of rivers (Hudec 1989;Czerniawski & Domagała 2012). The relatively high flow rate and high current speed favour the growth of plankton (Campbell 2002).…”
Section: Water-level Changes and Flooding Eventsmentioning
confidence: 98%
“…Moreover, the vast majority of small water bodies undergo the process of terrestrialisation, which may result in negative implications for biodiversity. Not only will the concentration of nutrients structure the assemblages of plankton in small water bodies, but physical factors will also play a role Wilk-Woźniak et al, 2011;Czerniawski and Domagała, 2012). However, in ecosystems with varying environmental conditions, organisms have to adapt in order to survive and develop.…”
Section: Introductionmentioning
confidence: 99%